Potensi Resin Damar Mata Kucing dengan Resin Damar Batu Berdasarkan Perbedaan Nilai Kekerasan - Vara, Varisati Nalina; Takarini, Veni; Usri, Kosterman (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Indonesia is one of the world’s resin producers with high species variability. During this time, natural resins that are widely used and circulating in the market are resin damar mata kucing and resin damar batu. Both of these resins damar come from different types of trees and harvesting methods. The research aims to determine the differences in the value of the hardness of the two resins, so that it can be considered of the resin damar uses as basic materials in dentistry. Hardness test was performed on 16 resin samples of resin damar mata kucing and 16 resin samples of resin damar batu using the Shore Hardness Tester (Shore D Durometer) method based on ASTM D2240. From the results of the study obtained an average value of resin damar mata kucing hardness is 35 Hard Durometer, while the average value of resin damar batu hardness is 43 Hard Durometer. Its can be caused by different types of trees and how they are harvested. Resin damar batu are fossilized sap and obtained from Shorea eximia trees by means of collection from the ground. In general, resin damar batu is blackish brown. Meanwhile, yellowish-clear resin damar mata kucing is a resin damar that has less ash and dirty content, because of the way of harvesting is done by tapping directly on the Shorea javanica trees. So, resin damar batu have a higher hardness value than resin damar mata kucing. It can be concluded that resin damar mata kucing and resin damar batu have different values of hardness, which have potentiality as basic materials in dentistry.